BAHASA PESAN DALAM PROSES PENULISAN NASKAH PADA PROGRAM INFOTAINMENT KISS PAGI DI INDOSIAR - Ria Yunita (Jurnal Komunikasi, 2018)
Infotainment, the packaging of the event wrapped and inserted with entertainment to attract the attention of audiences. based on information, which also contains entertainment content in order to increase popularity. This study aims to find out the language of the message on the process of writing the script on KISS PAGI program in INDOSIAR. The framework of thinking used, mass communication, media, tetevisi,, the type of television program, and the language of the message in the process of writing on KISS PAGI program in Indosiar. The research is interpretative using semiotic analysis research method. Semiotics Saussure review the subject of this study because it is considered very appropriate in assessing the sign and meaning especially in the scope of text and language. Research results there is a language message on the process of writing a script that can affect the view of the audience on the impressions. memorable in the eyes of the audience. Keywords: language messages, scriptwriting, infotainment